PEMENUHAN ATAS SARANA DAN UTILITAS PADA PERUMAHAN SUBSIDI MUTIARA PURI HARMONI RAJEG TANGERANG MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 2011 TENTANG PERUMAHAN DAN PERMUKIMAN - Muhammad Aziz Nurhakim; Endang Pandamdari (Jurnal Hukum Adigama, 2018)
There are so many housing developers that didn’t do their jobs and fulfilling their obligations properly when it comes to providing means, utilities, and infrastructures required in a housing complex. As an example: Vista Land Group Limited as the developer for Mutiara Puri Harmoni housing in Rajeg. The main issue of this research is juridical review of providing a housing complex with facilities required and applied sanctions if a developer didn’t fulfill their obligations properly. The author is interested on researching this subject because other than research location that is close with writer’s residence, Rajeg is a fast developing area where the inhabitants own massive lands, one of them being Mutiara Puri Harmoni housing; 50 Ha in total width. In order to gain data required for the research, the writer decided to use normative research method with library study for secondary, primary legal matters, non-legal matters, and completed with few interview results. In conclusion: Vista Land Group Limited is liable for providing low quality water supply, road network’s lightings, and public cemetery as stated in Article no. 4 section (1)a, section (3) a and g, and article no.9 chapter (2) Regulation of the Tangerang District No.4 year 2012, and Article no. 134 of the 2011 housing and settlement act no. 11. It’s better for Tangerang district government to start doing supervision to housing developers in Tangerang so this kind of cases won’t happen again.